Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This paper documents two aspects of Canada's regional diversity and compares the results with those across U.S. regions. Although gradually converging, Canadian provinces exhibit a considerably diverse economic structure. The paper suggests that the reduction in macroeconomic volatility in Canada after the introduction of inflation targeting is largely attributable to the reaction of the private sector to the establishment of a credible monetary policy framework. Reduction in personal income taxation provides considerably larger efficiency gains than a reduction in the effective Goods and Services Tax (GST).